Public opinion and media narratives on the motivations behind the ASEAN declaration on technology-based human trafficking - Muhammad Zahrul Anam; Mutiara Dwi Sari (Universitas Islam Malang, 2026)
The 2023 ASEAN Summit in Labuan Bajo, Indonesia, issued a declaration to combat technology-based trafficking across the ASEAN region. The emergence of this declaration is an immediate response of ASEAN members, especially Indonesia, to current cases of human trafficking in which perpetrators have utilized technology. According to the United Nations High Commissioner for Human Rights, criminal syndicates are forcing hundreds of thousands of people into online criminal activities in Southeast Asia, ranging from illicit gaming to cryptocurrency fraud and romance investment schemes. Individuals who are compelled to labor in these fraud operations are subjected to inhuman treatment while being made to commit crimes. This article aims to investigate the motivation behind the declaration through social media users and online news publishers. The collected data is from selected online news sources: Antara News, Jakarta Globe, Kompas, Reuters, Tempo.co, The Diplomat, and Viva.co.id, along with comments from YouTube and Instagram. Following that, data analysis is conducted using NVivo 12. The paper applies Albert Bandura's social cognitive theory. The declaration was motivated by observational learning and self-efficacy. Then, public opinion, in the context of social cognitive theory, is understood as a form of social persuasion.